A produção oral em Língua Inglesa: Atividades teatrais como possibilidade - Jorge, Elza da Glória (2006)
The research aims at investigating the learning perceptions and feelings students reveal when exposed to theater activities. The theoretical bases for this study are Parâmetros Curriculares Nacionais Língua Estrangeira (1998), the sociointeracionist approach proposed by Vygotsky (1998), as well as some theater concepts presented by Spolin (1963) and Reverbel (2002). This study was conducted in the teacher-researcher s classroom with 5 students of the 6th grade of a public school in São Paulo. The data were collected in the second semester of 2004 by questionnaires, interviews, minute notes, and teacher s digital diaries. In relation to the learning process, the results revealed perceptions about several contents: linguistic knowledge, vocal techniques, body techniques and theater concepts. In relation to feelings, perceptions belonging to didactic, interpersonal and personal orders were identified. These results show that the use of theater activities in the classroom can develop students oral production and can also promote the development of the human being and citizenship